Radicalization’s Core - Derfoufi, Zin (Terrorism and political violence, 2022)
Is radicalization inherently conducive to terrorism? This paper addresses this fault-line within discourses on radicalization by analyzing the political awakening and mobilization of British Muslims operating in environments targeted by violent-extremists. The results show that despite undergoing the “root causes” and “triggers” associated with radicalization, and even having direct contact with violent-extremists, research participants still rejected terrorism. This paper analyzes why participants’ radicalism promoted resilience to political violence rather than propel them toward it. It challenges the selection bias within terrorism and radicalization studies which constrain our ability to understand this phenomenon by focusing on the rare cases of people who support terrorism while ignoring its more common trajectories of non-terror related activism (or apathy). In correcting this bias, this paper proposes a more holistic definition of radicalization grounded in the lived realities of people undergoing that process and concludes with a discussion on what the findings mean for the assumptions underpinning academic discourses on this matter and state counterterrorism policies.